351. X-ray protective clothings policy. (December 2018) - Ostinelli, A.; Cacciatori, M.; Vassena, A.; Berlusconi, C.; Lattuada, P.; Molinari, P.; Frigerio, M.; Duchini, M.
Abstract : Purpose: The main problem associated with the use of X-ray protective clothings is the deterioration and the damages that reduce their efficiency. To overcome this risk, periodic integrity checks are required. At the ASST Lariana a dedicated procedure was developed in order to assess the suitability for use, exploiting acquisition and processing of digital radiographic images. Methods: A dedicated database was realized to record all the relevant information and to ensure the control traceability. Two imaging procedures were adopted, depending on the availability of a X-ray fluoroscopic digital system or a CT scanner. Both allowed to acquire the image of the entire device: the first performs a spatial scan by sliding the table while the latter provides a scout image. The recognition and weighing of defects and breaks was carried out both manually, by evaluating the area of a ROI containing the damage, and with a semiautomatic approach by means of an in house software developed in MatLab environment (see Fig.). According to recent INAIL 2016 recommendations, all protective clothings with surface defects >15 mm 2 located in the immediate vicinity of a vital organ were rejected. If the defects were not in proximity of a vital organ and had a ⩽670 mm 2 surface, the test was considered passed. Results: By applying the defect criteria rejection to the examined samples, only 11 out of the 188 controls, corresponding to 5.9% of the tested X-ray protective garments, were rejected. For 20 protective clothes (10.6%) a judgment of partial suitability was issued. All rejected devices have been used for more than seven years. Conclusions: The test results allowed to completely define the suitability for use and, eventually, to activate the substitution practices. The adopted control procedure requires technologies that are normally present in hospitals and ensures repeatability, traceability and reliability.